Photoswitchable hydrazones with pyridine-based rotors and halogen substituents - Kotásková, Lucie; Jewula, Pawel; Herchel, Radovan; Nemec, Ivan; Neugebauer, Petr (ROYAL SOC CHEMISTRY, 2024)
The Z,E-photoisomerization of pyridine-based hydrazone switches is typically suppressed due to the presence of pyridine-based rotors. The crystal structures of studied compounds were investigated using theoretical methods combining DFT and QT-AIM calculations to unveil the nature and properties of the intramolecular hydrogen bonding. In this study, we introduced a new series of pyridine-based hydrazones anchored with o-halogen substituents (2-X) and investigated their photoswitching abilities using 1H NMR and UV-Vis spectroscopy. The efficiency of the photoisomerization from initial 2-X-Z to the 2-X-E isomer varied, with the highest yield observed for 2-Cl-E (55%). Our findings, supported by DFT calculations, revealed the formation of a new diastereomer, 2-X-E*, upon back-photoisomerization. We demonstrated that hydrazones from the 2-X series can be reversibly photoswitched using irradiation from the UV-Vis range, and additionally, we explored the effect of the halogen atom on their switching capabilities and also on their thermodynamics and kinetics of photoswitching, determining their molecular solar thermal energy storage potential. We report on the E,Z-photoisomerization of hydrazone switches with pyridine-based rotors and halogen-substituted stators.

The Z,E-photoisomerization of pyridine-based hydrazone switches is typically suppressed due to the presence of pyridine-based rotors. The crystal structures of studied compounds were investigated using theoretical methods combining DFT and QT-AIM calculations to unveil the nature and properties of the intramolecular hydrogen bonding. In this study, we introduced a new series of pyridine-based hydrazones anchored with o-halogen substituents (2-X) and investigated their photoswitching abilities using 1H NMR and UV-Vis spectroscopy. The efficiency of the photoisomerization from initial 2-X-Z to the 2-X-E isomer varied, with the highest yield observed for 2-Cl-E (55%). Our findings, supported by DFT calculations, revealed the formation of a new diastereomer, 2-X-E*, upon back-photoisomerization. We demonstrated that hydrazones from the 2-X series can be reversibly photoswitched using irradiation from the UV-Vis range, and additionally, we explored the effect of the halogen atom on their switching capabilities and also on their thermodynamics and kinetics of photoswitching, determining their molecular solar thermal energy storage potential. We report on the E,Z-photoisomerization of hydrazone switches with pyridine-based rotors and halogen-substituted stators.
Photoswitchable hydrazones with pyridine-based rotors and halogen substituents
Keywords: ISOMERIZATION MECHANISM; BASIS-SETS; CRYSTAL; PH; ISOMERIZATION MECHANISM; BASIS-SETS; CRYSTAL; PH